Efficient intertemporal allocations with recursive utility. - Dumas, Bernard; Uppal, Raman; Wang, Tan (Journal of Economic Theory, 2000)
In this article, our objective is to determine efficient allocations in economies with multiple agents having recursive, non-time-additive utility functions. Our main result is to show that in a multi-agent economy, the problem of determining efficient allocations can be characterized in terms of a single value function (that of a social planner), rather than multiple functions (one for each investor), as has been proposed thus far (D. Duffie et al., 1994, J. Math. Econ. |Wb23[|WB], 133–146). We then show how the single value function can be identified using the familiar technique of stochastic dynamic programming. Journal of Economic Literature Classification Numbers: D81, D61, D91, C61. Copyright 2000 Academic Press.